PENTINGNYA PENDIDIKAN ETIKA SEKSUALITAS MENURUT HINDU BAGI GENERASI MUDA HINDU - I Nyoman Hari Mukti Dananjaya; Ni Ketut Puspita Sari (Guna Widya: Jurnal Pendidikan Hindu, 2022)
In the midst of free development in today's era of globalization, there have been many widespread sexual deviations committed by young people. Lack of sex ethics education which has caused many problems and violation of norms. It has also led to a free and unhealthy sex life and disease. This sexual deviation often occurs among young people such as pregnancy out of wedlock, abortion, rape, cohabitation and others. Factors for the occurrence of these sexual deviations can be seen in the internal factors contained within themselves and external factors contained in their environment. Sex and the issues related to it should be studied well before one enters marriage. Many young people are familiar with sex, but their introduction to sex is not deep into the science of sex. The desire to know sex is a tendency of basic human traits, so it's time for this to be satisfied by providing proper sex and health education. Lack of education about sex among young people causes and exposes themselves to be obscene, cheap, free, and creates a permissive attitude of free sex that makes them lie and destroy. This unfortunate situation will eventually lead to conflict between young people and their families, especially parents. Keywords: Ethics, Sex Education